Using a free open source software to teach mathematics. Issue 4 (10th May 2012) - Botana, Francisco; Abánades, Miguel A.; Escribano, Jesús
ABSTRACT We present the experience of the authors teaching mathematics to freshmen engineering students with the help of the open source computer algebra system Sage. We describe some teaching resources and present an ad hoc distribution of Sage used by the authors.© 2012 Wiley Periodicals, Inc. Comput Appl Eng Educ 22:728–735, 2014; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21565